Solving Delay Differential Equations Using Explicit Runge-Kutta Method - Aung, San Lwin (2004)
Introduction to delay differential equations (DDEs) and their examples are presented. The General formulation of Explicit Runge-Kutta method when adapted to delay differential equations is described.